Imaging techniques for cardiac strain and deformation: comparison of echocardiography, cardiac magnetic resonance and cardiac computed tomography. (February 2013) - Tee, Michael; Noble, J. Alison; Bluemke, David A
Myocardial function assessment is essential for determining the health of the myocardium. Global assessment of myocardial function is widely performed (by estimating the ejection fraction), but many common cardiac diseases initially affect the myocardium on a regional, rather than global basis. Regional myocardial wall motion can be quantified using myocardial strain analysis (a normalized measure of deformation). Myocardial strain can be measured in terms of three normal strains (longitudinal strain, radial strain and circumferential) and six shear strains. Cardiac MRI (cMRI) is usually considered the reference standard for measurement of myocardial strain. The most common cMRI method, termed tagged cMRI, allows full, 3D assessment of regional strain. However, due to its complexity and lengthy times for analysis, tagged cMRI is not usually used outside of academic centers. Tagged cMRI is also primarily used only in research studies. Echocardiography combined with tissue Doppler imaging or a speckle tracking technique is now widely available in the clinical setting. Myocardial strain measurement by echocardiography shows reasonable agreement with cMRI. Limited standardization and differences between vendors represent current limitations of the technique. Cardiac computed tomography (CCT) is the newest and most rapidly growing modality for noninvasive imaging of the heart. While CCT studies are most commonly applied to assess the coronary arteries, CCT is easily adapted to provide functional information for both the left and right ventricles. New methods for CCT assessment of regional myocardial function are being developed. This review outlines the current literature on imaging techniques related to cardiac strain analysis and discusses the strengths and weaknesses of various methods for myocardial strain analysis.